Coconut Carbon Sequestration Part 1 / Highlights on Carbon Cycle in Coconut Plantations - O. Roupsard; N. Lamanda; C. Jourdan; M. Navarro; I. Mialet-Serra; J. Dauzat; Tiata Sileye (International Coconut Community, 2008)
This article reviews scientific information in order to prepare application of coconut plantations to the Clean Development Mechanism CDM of the Kyoto Protocol. It sums up some theories for describing the C cycle within a given plantation, separating the coconut trees, the under-storey and the soil. It synthesizes recent reports about the C cycle (stocks and fluxes) of a chronosequence of coconut plantations, considered to be a reference for productivity (high level of fertility, no drought). It gives figures for the potential C balance of a coconut plantation and compares them to other tropical humid evergreen forests. Although the results should not be extrapolated without caution, they highlight some main traits of this peculiar crop, such as a high productivity and a large C allocation into organs displaying rapid turnover (bunches of fruits, fine roots, leaves, peduncle and spikelets), the fate of which is to be turned into litter. Moreover, results bring new insights into the physiology of this plant, which is of high interest for understanding the components of yield, such as reserve dynamics. They also confirm that litter management is crucial for the C fixation and the sustainability of coconut cultivation, especially when the levels of inputs are low.